(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article represents an analysis of the utterance with the meaning of preference in light of their semantic peculiarities. The preference attributing illocutionary force to an utterance has specific semantic characteristics formed on the base of the meaning of operational comparative valuation.